Vanillin, a key-intermediate of biobased polymers. (July 2015) - Fache, Maxence; Boutevin, Bernard; Caillol, Sylvain
Graphical abstract: Highlights: Vanillin is one of the only industrially available aromatic products from lignin. Vanillin is also a non-toxic substance. Various biobased aromatic monomers were prepared from this compound. Several polymers were synthesized. Vanillin is to become a key-intermediate for biobased aromatic polymers. Abstract: The use of vanillin for the preparation of renewable polymers is reviewed in this work. The synthesis of polymers from renewable resources is a burning issue that is actively investigated. Vanillin is currently one of the only biobased and aromatic compounds that are industrially available. For this reason, vanillin recently gained much attention from the polymer community. The first part of this work aims at giving an overview of the different existing sources of vanillin, and of their relevance in the context of a potential use in polymer science. The second part of this work sums up the efforts of the scientific community to prepare a wide range of vanillin-based polymers, e.g. phenolic, epoxy and benzoxazine resins, polyesters, acrylate and methacrylate polymers. The interest in the use of vanillin to prepare renewable polymers is recent but the number of contributions on this subject is growing fast.